Analisis Sentimen Publik pada Tagar #KawalPutusanMK di Media Sosial X - Syafreza Fachlevi; Andi Alimuddin Unde; Hasrullah Hasrullah (Syntax Corporation Indonesia, 2024)
The background of this study is that various sentiments around the community began to emerge due to the hashtag that recently appeared on social media X (Twitter), namely the hashtag of the #KawalPutusanMK movement that emerged as a form of public resistance to the efforts of the House of Representatives (DPR) to change the decision of the Constitutional Court (MK) related to the 2024 Regional Elections. The movement sparked various controversies among the public, academics, politicians, and political observers. Although many support this movement, not a few also refuse. Therefore, this study aims to analyze public sentiment towards #KawalPutusanMK hashtags on social media X (Twitter), using a netnography approach and big data analysis. The #KawalPutusanMK movement emerged in response to the DPR's efforts to revise the Constitutional Court's (MK) decision regarding the 2024 Regional Elections, which sparked controversy among the public. The research data was taken from conversations that occurred on platform X between August 21 and September 29, 2024. The results of the analysis showed that there were 1127 tweets using the hashtag, with the following sentiment distribution: 91 positive, 484 negative, and 552 neutral. The dominance of negative sentiment indicates public dissatisfaction with the Constitutional Court's decision. This research contributes to understanding political communication patterns on social media and provides insights for the government in monitoring public opinion and formulating more responsive policies.